Administrative, Cultural, Urban and Economic Conditions in Jerusalem in the Early Abbasid Period (132-247 AH/749-861 AD) - Obeidat, Adnan Abdulla (Jordan Journal for History and Archaeology, 2021)
This article sheds light on the history of the city of Jerusalem during the early Abbasid period (132-247 AH/749-861 AD), after the city had reached the most advanced stages of architectural and cultural development in the Umayyad period, based on it being a religious and political center competing with the Two Holy Mosques in the Hijaz. After the fall of the Umayyad Caliphate, the political role of the city of Jerusalem lessened, once the center of the caliphate moved to Baghdad, despite the continued care of the Abbasid caliphs for the city, especially regarding restorations of the holy sites, after the natural disasters that afflicted the city. The study also sheds light on the cultural and economic role of the city during the period.